Pharmacogenetics of FSH Action in the Male - Schubert, Maria; Pérez Lanuza, Lina; Gromoll, Jörg (Frontiers in Endocrinology, 2019)
Male infertility is a major contributor to couple infertility, however in most cases it remains “idiopathic” and putative treatment regimens are lacking. This leads to a scenario in which intra-cytoplasmic spermatozoa injection (ICSI) is widely used in idiopathic male infertility, though the treatment burden is high for the couple and it entails considerable costs and risks. Given the crucial role of the Follicle-stimulating hormone (FSH) for spermatogenesis, FSH has been used empirically to improve semen parameters, but the response to FSH varied strongly among treated infertile men. Single nucleotide polymorphisms (SNPs) within FSH ligand/receptor genes (FSHB/FSHR), significantly influencing reproductive parameters in men, represent promising candidates to serve as pharmacogenetic markers to improve prediction of response to FSH. Consequently, several FSH-based pharmacogenetic studies have been conducted within the last years with unfortunately wide divergence concerning selection criteria, treatment and primary endpoints. In this review we therefore outline the current knowledge on single nucleotide polymorphisms (SNPs) in the FSH and FSH receptor genes and their putative functional effects. We compile and critically assess the previously performed pharmacogenetic studies in the male and propose a putative strategy that might allow identifying patients who could benefit from FSH treatment.